The Influence of External Information on Collective Bargaining: Survey Evidence of Union and Firm Negotiators in the Netherlands - Lehr, Alex; Akkerman, Agnes; Torenvlied, René (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2015)
This paper seeks to answer two questions: 1- To what extent are negotiators in collective bargaining influenced by different types of external information? 2- How can differences in the influence of external information between negotiators be explained by the characteristics of the negotiators and bargaining units? A standardized questionnaire measuring self-reported influences of different types of external information was developed and administered to a representative sample of union and firm negotiators in the Netherlands. In total, 123 negotiators participated in the survey. Four types of external information were investigated: 1- economic information; 2- information on organizational power; 3- institutional information; and 4- information spillovers. Descriptive analyses show that economic information, particularly when referring to the sector level, was very influential, as was institutional information on national and sectoral collective agreement developments. Information reflecting organizational power, e.g. militancy, carried less weight, while information on other bargaining events, i.e. spillover, was also very important. From extant theory, empirical findings and common assumptions in labour relations literature, the paper developed and tested a number of hypotheses concerning the influence of external information. It was found that the influence of spillovers increased with the proximity of their source. Union negotiators were generally more influenced by external information than firm negotiators. There was some evidence that influence increased with experience, but this effect was rather modest. Evidence that negotiators in sector bargaining were less affected by the economic environment than negotiators in company bargaining was weak, but they were found to be less influenced by spillovers and international collective agreement developments.